Pengaruh Limbah Padat Pabrik Kertas Rokok Terhadap Beberapa Sifat Kimia Tanah Ultisol Tambunan A - Melina Vika; Kemala Sari Lubis; M. M. B. Damanik (Universitas Sumatera Utara, 2017)
Solid waste of cigarette paper factory does not contain hazard and toxic materials but contain CaCO3as a lime material. The research of was conducted to study effect of application of solid waste fromthe cigarette paper factory to improve soil properties at Ultisol Tambunan A. This research wasconducted at the Laboratory of Soil Physics, Agriculture Faculty and analytic laboratory of socfindocompany from May until June 2016. The research used non factorial completely randomized designconsist (CRD) of four (4) treatment solid waste (cigarette paper factory) and five (5) replications,there are: L0 (control), L1 (0,4 g), L2 (0,6 g), and L3 (0.8 g). The results showed that the applicationof solid waste from cigarette paper significantly increase soil pH, P-available, Ca-exchangeble butnot significantly increase K-exchangeable and organic carbon of Ultisol. Application of solid wastefrom cigarette paper significantly decrease Al-exchangeable and no significantly decrease Alsaturatedof Ultisol.Keyword : Solid waste of cigarette paper, Ultisol